MENINGKATKAN KECAKAPAN KEWARGANEGARAAN (CIVIC SKILL) MELALUI PEMBELAJARAN PKN BERBASIS PROJECT CITIZEN (STUDI KUASI EKSPERIMEN DI SMK YPT BANJARMASIN) - Norlaili Hidayati (Universitas Lambung Mangkurat, 2013)
Project Citizen is a learning model that able to improve the skills of citizenship education including intellectual skills and participation skills. Project Citizen is a portofolio-based learning model. This study uses a quantitative approach. The method used is a quasi experimental design with